Synergistic Hurdle Effect of Physical and Chemical Treatments for Non-thermal Pasteurization of Guava (Psidium guajava) Juice - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2020)
Guava (Psidium guajava) is commonly known for its food and nutritional values throughout the world. It has high fermentable sugar composition when mature and ripe .It’s known for its sweet and tangy flavor and many uses. It is a fruit with good nutritional attributes but has short shelf-life under the ambient conditions. Dimethyl dicarbonate is a microbial control agent inhibitor widely applied in the food industry. Various current and potential applications of ultrasound in the fruit processing have been identified. Consumers prefer to safe, nutritious, high quality guava juices without thermal treatment. In our research, synergistic or hurdle effectiveness by ultrasound combined dimethyl dicarbonate was studied on guava juice. Different parameters of ultrasonic duration (10, 15, 20, 25, 30 min), dimethyl dicarbonate addition (10, 15, 20, 25, 30 µL/100mL) was examined on guava juice in respect of microbial inactivation. Log10 reductions of total plate count and coliform were evaluated to define the optimal variables. Our results revealed that microbial loads in guava juice would be decreased dramatically by ultrasonic treatment in 25 minutes at frequency 37 kHz with 20 µL/100mL supplementation of dimethyl dicarbonate to create a synergistic hurdle effect for a significant microbial reduction. It could be considered as an excellent non-thermal pasteurization for a better fruit juice quality, not only for guava but also for other tropical fruits to enhance their added value.Keywords: Guava juice, Synergistic, Hurdle, Ultrasound, Dimethyl dicarbonate, Microbial reduction.